Neither Man nor Woman: Berdache — A Case for Non-Dichotomous Gender Construction - Schnarch, Brian (Anthropologica, 2022)
How many genders are there? The notion that gender is inevitably dichotomous is strongly challenged by the historical and contemporary existence of the berdache status in many North American societies. A preliminary conceptual framework for the analysis of sex/gender systems is proposed. The berdache status as understood in the English-language ethnographic literature is summarized. The traditional characterization of the status (e.g., institutionalized homosexuality or transvestite) are criticized and alternative categorizations of — "male" and "female" — berdaches, as third and fourth genders, are presented. Considered in this light, gender as a dichotomous classification system is seen to be a cultural construct. The implications of this conclusion for feminist theorizing are explored.